Flaky catalyst and preparation method thereof, carbon nanotube array and preparation method thereof, conductive agent, pole piece and battery

By controlling the order of metal precipitation and the degree of supersaturation of the solution during the catalyst preparation process, a sheet-like catalyst with high surface density was obtained, which solved the problem of too low surface density and insufficient support of the existing catalyst, and achieved efficient growth of large-diameter and long-array carbon nanotubes and the construction of an excellent conductive network.

CN119588360APending Publication Date: 2025-03-11YONGJIANG LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411996393.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing catalysts used to grow carbon nanotubes face problems such as too low metal particle density, small substrates resulting in insufficient support, and mutual interference between carbon nanotubes grown on different substrates, making it difficult to realize long array carbon nanotubes.

Method used

The precursor was obtained by mixing a salt solution containing M2+, M3+ and Q ions with a precipitant solution, and a flake catalyst was obtained by calcining and reduction processes. During the preparation process, this method controls the order of metal precipitation and the degree of supersaturation of the solution, obtains a large-sized hydrotalcite sheet substrate, and makes the active metal precipitate preferentially in the central area, increasing the surface density of the active metal distribution.

Benefits of technology

It has achieved efficient growth of large-diameter and long-array carbon nanotubes, built an excellent conductive network, and improved the performance of carbon nanotubes in the fields of composite material enhancement and electrochemical energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588360A_ABST
    Figure CN119588360A_ABST
Patent Text Reader

Abstract

The invention provides a flaky catalyst and a preparation method thereof, a carbon nanotube array and a preparation method thereof, a conductive agent, a pole piece and a battery. The preparation method of the flaky catalyst comprises the following steps: performing primary mixing on a salt solution containing M < 2 + >, a salt solution containing M < 3 + > and a salt solution containing Q ions to form a first mixed solution; mixing a precipitant with a solvent to form a second mixed solution; the first mixed solution and the second mixed solution are mixed to form a third mixed solution, and a precursor is obtained through coprecipitation; and calcining and reducing the precursor to obtain the flaky catalyst. Therefore, the large-size hydrotalcite lamellar substrate is obtained, the active metal is preferentially precipitated in the central area of hydrotalcite, the surface density of active metal distribution under the same loading capacity is increased, in the process of preparing the carbon nanotube array, the active metal in the central area catalyzes growth of the carbon nanotubes and can protect the internal carbon nanotubes, and the performance of the carbon nanotube array is improved. Therefore, the large-diameter and long-array carbon nanotubes are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of materials, and specifically, to a sheet catalyst and a preparation method thereof, a carbon nanotube array and a preparation method thereof, a conductive agent, a pole piece, and a battery. Background Art

[0002] As a typical new type of nanomaterial, carbon nanotubes have excellent mechanical, electrical, optical and thermal properties. They have broad application prospects in the fields of composite material reinforcement, electrochemical energy storage, electronic devices, etc. and have attracted much attention.

[0003] According to the different forms of self-assembly, carbon nanotubes can be divided into intertwined cluster structures and directional array structures. In the application of carbon nanotubes, the intertwined and entangled behavior between carbon nanotubes in the cluster structure makes it difficult for them to grow fully and disperse effectively, thus limiting their performance in fields such as composite material reinforcement. In contrast, the carbon nanotube array structure has consistent orientation, high purity, large aspect ratio and easy dispersibility. After dispersion, the original length of the carbon nanotube array can be maintained, and an excellent long-range conductive network can be constructed, fully demonstrating the excellent properties of carbon nanotubes in fields such as electrochemical energy storage.

[0004] The catalyst structure greatly affects the performance of the grown carbon nanotubes. Catalyst metal particles are usually loaded on the surface of a substrate. Commonly used micron-sized substrates, such as vermiculite, metal oxides, graphite sheets, hydrotalcite-like compounds, etc., have a flat surface and a high specific surface area. The metal particles are loaded on the surface to make a sheet catalyst, which can be effectively used to prepare array-shaped carbon nanotubes.

[0005] However, the catalysts currently used to grow carbon nanotubes still face many problems, including the metal particle surface density is too low to form effective synergistic growth, the small substrate leads to insufficient support for the carbon nanotube array and difficulty in full growth, and mutual interference between carbon nanotubes grown on different substrates, etc., resulting in the growth of long arrays of carbon nanotubes is still difficult to achieve. Summary of the invention

[0006] The present application aims to solve one of the technical problems in the related art at least to some extent.

[0007] The first aspect of the present application provides a method for preparing a sheet catalyst, the method comprising: 2+ The salt solution containing M 3+ A salt solution containing Q ions is mixed once to form a first mixed solution, wherein the M 2+ Including Mg 2+ 、Zn 2+ , Ca 2+ , Mn 2+ At least one of the M3+ Including Cr 3+ 、Al 3+ 、Ru 3+ At least one of the Q ions includes Fe 2 + , Fe 3+ 、Co 2+ 、Co 3+ 、Ni 2+ , Cu 2+ at least one of the following: mixing a precipitant with a solvent to form a second mixed liquid; mixing the first mixed liquid and the second mixed liquid to form a third mixed liquid, and obtaining a precursor by co-precipitation, wherein the temperature of the third mixed liquid during the co-precipitation process is 90°C-150°C, and the pH of the third mixed liquid is 4-12; calcining and reducing the precursor to obtain the flaky catalyst.

[0008] Therefore, in the process of preparing the flaky catalyst, the present application obtains a large-sized hydrotalcite lamellar substrate by mixing the first mixed solution and the second mixed solution, and controlling the order of metal precipitation and the degree of supersaturation of the solution, and the active metal is preferentially precipitated in the central area of ​​the hydrotalcite, and there is no active metal in the edge area of ​​the hydrotalcite, thereby increasing the surface density of the active metal distribution under the same loading amount. In the process of preparing the carbon nanotube array, the active metal in the central area catalyzes the growth of the carbon nanotubes and can protect the internal carbon nanotubes, thereby obtaining large-diameter, long-array carbon nanotubes.

[0009] According to some embodiments of the present application, the method satisfies at least one of the following conditions: the molar concentration of the precipitant solution is 0.1 mol / L-20 mol / L; the precipitant includes at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate, ammonium bicarbonate, urea, and ammonia water. Thus, the supersaturation degree of the solution is regulated to obtain a large-sized lamellar structure.

[0010] According to some embodiments of the present application, the first mixed solution contains M 2+ 、M 3+ The sum of the concentrations of Q ions is 0.005 mol / L-2 mol / L. Thus, the degree of supersaturation of the solution is regulated to obtain a large-sized lamellar structure.

[0011] According to some embodiments of the present application, the first mixed solution contains M 2+ With M 3+ The molar ratio of Q ions and M in the first mixed solution is 0.1-10. 3+ The molar ratio of is 0.01-2. Thus, the supersaturation degree of the solution is regulated to obtain a large-sized lamellar structure.

[0012] According to some embodiments of the present application, the method satisfies at least one of the following conditions: the calcination atmosphere is an inert gas or air; the calcination temperature is 400°C-900°C; the calcination heating rate is 1°C / min-20°C / min.

[0013] According to some embodiments of the present application, the reduction process includes: pretreating the calcined precursor by a pretreatment gas, and the pretreatment satisfies at least one of the following conditions: the pretreatment temperature is 400°C-900°C; the pretreatment time is 1min-60min.

[0014] The second aspect of the present application provides a sheet catalyst, which is prepared by the method provided by the first aspect of the present application, wherein the sheet catalyst includes a carrier, the surface of the carrier includes a central region and an edge region, and the active metal particles are only distributed in the central region. Thus, the active metal particles in the central region can promote the growth of carbon nanotubes during the preparation of carbon nanotubes, protect the internal carbon nanotube array, thereby promoting the continuous growth of arrayed carbon nanotubes to form large-diameter, long array carbon nanotubes.

[0015] According to some embodiments of the present application, the sheet diameter of the sheet catalyst is 2 μm-10 μm, the sheet thickness is 50 nm-200 nm, and the average particle size of the active metal particles is 2 nm-50 nm. Thus, the sheet catalyst has a large-size sheet structure, and the average particle size of the active metal particles is large, which can promote the efficient growth of the carbon nanotube array.

[0016] The third aspect of the present application provides a method for preparing a carbon nanotube array, the method comprising: mixing the sheet catalyst prepared by the method provided by the first aspect of the present application or the sheet catalyst provided by the second aspect of the present application with a carbon source gas for reaction, wherein the reaction temperature is 500°C-900°C to obtain the carbon nanotube array. Thus, large-diameter, long-array carbon nanotubes are obtained, and a conductive network with excellent performance can be constructed.

[0017] The fourth aspect of the present application provides a carbon nanotube array, which is prepared by the method provided in the third aspect of the present application, wherein the length of the carbon nanotube array is 20 μm-200 μm, and the number of walls of the carbon nanotubes in the carbon nanotube array is 2-30 layers.

[0018] The fifth aspect of the present application provides a conductive agent, including the carbon nanotube array provided by the fourth aspect of the present application.

[0019] The sixth aspect of the present application provides a pole piece, comprising the conductive agent provided in the fifth aspect of the present application.

[0020] The seventh aspect of the present application provides a battery, comprising the electrode provided in the sixth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0022] Figure 1 A schematic flow chart of a method for preparing a sheet catalyst according to an embodiment of the present application is shown.

[0023] Figure 2 A typical transmission electron microscope photograph showing the distribution of metal particles in the central area of ​​the carrier after pretreatment of the catalyst prepared in Example 1 of the present application.

[0024] Figure 3 This is a scanning electron microscope photograph of the catalyst prepared in Example 2.

[0025] Figure 4 This is the elemental analysis result of the catalyst prepared in Example 3.

[0026] Figure 5 This is a typical low-magnification scanning electron microscope photograph of the long array carbon nanotubes prepared in Example 3.

[0027] Figure 6 This is a typical high-magnification scanning electron microscope photograph of the long array carbon nanotubes prepared in Example 4.

[0028] Figure 7 This is a typical low-magnification scanning electron microscope photograph of the array carbon nanotubes prepared in Comparative Example 1.

[0029] Figure 8 This is a thermogravimetric analysis curve of the long array carbon nanotubes prepared in Example 4 under air atmosphere.

[0030] Reference numerals:

[0031] 11: carrier; 12: active metal particles. DETAILED DESCRIPTION

[0032] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0033] At present, flat silicon wafers are used as substrates, and metal particles are loaded on them by coating, evaporation or passing precursors. Although array-shaped carbon nanotubes can be grown, high-yield carbon nanotube growth cannot be achieved due to the low specific surface area of ​​the substrate. Micron-sized lamellar catalysts not only have a high specific surface area, but also provide a relatively flat surface that helps the growth of array-shaped carbon nanotubes, but there are still some problems that limit the length of the carbon nanotube array. First, the surface density of metal particles is often too low, resulting in excessive spacing between carbon nanotubes, making it difficult for them to produce a synergistic effect to form an array; secondly, there is mutual influence between arrays, especially in the early stages of carbon nanotube growth, these disturbances will make it difficult for carbon nanotubes to form an array-shaped growth; finally, the carbon nanotube array needs to continuously push away the nearby catalyst layer to continue to grow, which requires the carbon nanotube array to have a strong support force, but often due to the limited size of the catalyst layer (1μm-2μm), the carbon nanotube array is not thick enough and the support force is difficult to maintain continuously. Therefore, it is necessary to develop a catalyst with larger catalyst sheet size, high metal surface density and the ability to protect the growth of carbon nanotubes, so as to catalyze the efficient growth of long array carbon nanotubes.

[0034] The present application provides a method for preparing a catalyst, the method comprising: 2+ The salt solution containing M 3 + A salt solution containing Q ions is mixed once to form a first mixed solution, wherein the M 2+ Including Mg 2+ 、Zn 2+ , Ca 2+ , Mn 2+ At least one of the M 3+ Including Cr 3+ 、Al 3+ 、Ru 3+ At least one of the Q ions includes Fe 2+ , Fe 3+ 、Co 2+ 、Co 3 + 、Ni 2+ , Cu 2+ at least one of the following: mixing a precipitant with a solvent to form a second mixed liquid; mixing the first mixed liquid and the second mixed liquid at once to form a third mixed liquid, and obtaining a precursor by co-precipitation, wherein the temperature of the third mixed liquid during the co-precipitation process is 90°C-150°C, and the pH of the third mixed liquid is 4-12; calcining and reducing the precursor to obtain the flaky catalyst.

[0035] Therefore, in the process of preparing the flaky catalyst, the present application obtains a large-sized hydrotalcite lamellar substrate by mixing the first mixed solution and the second mixed solution once, and controlling the order of metal precipitation and the degree of supersaturation of the solution, and the active metal is preferentially precipitated in the central area of ​​the hydrotalcite, and there is no active metal in the edge area of ​​the hydrotalcite, thereby increasing the surface density of the active metal distribution under the same loading amount. In the process of preparing the carbon nanotube array, the active metal in the central area catalyzes the growth of the carbon nanotubes and can protect the internal carbon nanotubes, thereby obtaining large-diameter, long-array carbon nanotubes.

[0036] The method for preparing the flake catalyst proposed in the present application is described in detail below. Figure 1 , the method comprising:

[0037] S10: Preparation of M 2+ 、M 3+ , the first mixed solution of Q ions

[0038] According to some embodiments of the present application, 2+ The salt solution containing M 3+ A salt solution containing Q ions is mixed once to form a first mixed solution, wherein the M 2+ Including Mg 2+ 、Zn 2+ , Ca 2+ , Mn 2+ At least one of the M 3+ Including Cr 3+ 、Al 3+ 、Ru 3+ At least one of the Q ions includes Fe 2+ , Fe 3+ 、Co 2+ 、Co 3+ 、Ni 2+ , Cu 2+ At least one of .

[0039] According to some embodiments of the present application, the first mixed solution contains M 2+ 、M 3+ The sum of the concentrations of Q ions is 0.005 mol / L-2 mol / L. For example, it may be 0.005 mol / L, 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, etc., or may be a range consisting of any of the above values.

[0040] According to some embodiments of the present application, the first mixed solution contains M 2+ With M 3+The molar ratio of is 0.1-10, for example, it can be 0.1, 1, 3, 5, 7, 9, 10, etc., or can be a range composed of any of the above values.

[0041] According to some embodiments of the present application, the Q ions and M 3+ The molar ratio of is 0.01-2, for example, it can be 0.01, 0.05, 0.1, 0.5, 1, 2, etc., or can be a range consisting of any of the above values.

[0042] S20: preparing a second mixed solution containing a precipitant

[0043] According to some embodiments of the present application, a precipitant and a solvent are mixed to form a uniform second mixed solution, and the precipitant includes at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate, ammonium bicarbonate, urea, and ammonia water.

[0044] According to some embodiments of the present application, the molar concentration of the precipitant solution is 0.1mol / L-20mol / L, for example, it can be 0.1mol / L, 1mol / L, 5mol / L, 10mol / L, 15mol / L, 20mol / L, etc., or it can be a range consisting of any of the above numerical values.

[0045] S30: Mix the first mixed solution and the second mixed solution at once for co-precipitation to obtain a precursor

[0046] According to some embodiments of the present application, the first mixed liquid and the second mixed liquid are mixed in a reactor, nitrogen is continuously introduced into the reactor, and the third mixed liquid is heated and stirred at a temperature of 90°C-150°C, the pH is controlled to be 4-12, the stirring speed is 10rpm-600rpm, the precipitation time is 0.1h-36h, and the stirring is turned off and allowed to stand for a period of time. The standing aging time is 0.1h-36h. After the reaction is completed, the product is filtered, washed, dried, and crushed to obtain a precursor.

[0047] It should be noted that the "one-time mixing" referred to in the present application means that the first mixed solution and the second mixed solution are mixed before the reaction starts, rather than mixing them during the reaction. Before the reaction starts, the mixing method of the first mixed solution and the second mixed solution is not particularly limited. For example, the first mixed solution and the second mixed solution may be added to the reactor at the same time; or the second mixed solution may be added to the reactor first, and then the first mixed solution may be added to the reactor; or the first mixed solution may be added to the reactor first, and then the second mixed solution may be added to the reactor.

[0048] As an example, the heating temperature may be 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., etc., or may be a range consisting of any of the above values.

[0049] As an example, the pH during the coprecipitation process may be 4, 6, 8, 10, 12, etc., or may be in a range consisting of any of the above values.

[0050] Therefore, after the first mixed liquid and the second mixed liquid are mixed, the type of precipitated metal and the number of crystal nuclei produced can be regulated by controlling the pH, reaction temperature, type and concentration of the precipitant in the co-precipitation process, so that the active metal can be concentrated in the central area of ​​a carrier of a certain size, increasing the surface density of active sites under the same loading amount, making it easier for the catalyst to catalyze the preparation of long array carbon nanotubes.

[0051] S40: calcining and reducing the precursor to obtain the sheet catalyst

[0052] According to some embodiments of the present application, a precursor is placed in a reactor, an inert gas or air is introduced into the reactor, and the temperature is increased and calcined at a heating rate of 1° C. / min-20° C. / min.

[0053] As an example, the speed may be 1°C / min, 5°C / min, 10°C / min, 15°C / min, 20°C / min, etc., or may be a range consisting of any of the above values.

[0054] According to some embodiments of the present application, the calcination temperature may be 400°C-900°C, for example, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, etc., or may be a range consisting of any of the above numerical values.

[0055] According to some embodiments of the present application, the calcined precursor is placed in a reactor, and a pretreatment gas is introduced to reduce the precursor.

[0056] According to some embodiments of the present application, the pretreatment gas includes at least one of hydrogen, carbon monoxide, and methane.

[0057] According to some embodiments of the present application, the pretreatment temperature is 400°C-900°C, for example, it can be 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, etc., or it can be a range consisting of any of the above numerical values.

[0058] According to some embodiments of the present application, the pretreatment time is 1 min-60 min, for example, it can be 1 min, 10 min, 30 min, 45 min, 60 min, etc., or it can be a range consisting of any of the above numerical values.

[0059] As an example, the reactor may include at least one of a fixed bed, a fluidized bed, and a moving bed.

[0060] The second aspect of the present application provides a sheet catalyst, which is prepared by the method provided by the first aspect of the present application, wherein the sheet catalyst includes a carrier, the surface of the carrier includes a central region and an edge region, and the active metal particles are only distributed in the central region. Thus, the active metal particles in the central region can promote the growth of carbon nanotubes during the preparation of carbon nanotubes, and the edge region protects the carbon nanotube array in the central region, thereby promoting the continuous growth of the arrayed carbon nanotubes to form large-diameter, long arrayed carbon nanotubes.

[0061] In the present application, the radius of the catalyst layer is r, the central area of ​​the carrier refers to the range of 0-0.8r on the catalyst surface, and the edge area refers to the area other than the central area.

[0062] It should be noted that the size of the central region of the carrier can be designed according to the length and diameter of the carbon nanotube array to be prepared. For example, when a carbon nanotube array with a longer length and a larger diameter needs to be prepared, the reaction conditions of the coprecipitation can be adjusted to obtain a sheet catalyst with a larger central region and a higher surface density of active metal distribution at the same loading amount.

[0063] According to some embodiments of the present application, the sheet diameter of the sheet catalyst is 2 μm-10 μm, the sheet thickness is 50 nm-200 nm, and the average particle size of the active metal particles is 2 nm-50 nm. Thus, the sheet catalyst has a large-size sheet structure, and the average particle size of the active metal particles is large, which can promote the efficient growth of the carbon nanotube array.

[0064] In the present application, the sheet diameter, sheet thickness and average particle diameter of the sheet catalyst and the active metal particles can be statistically analyzed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM).

[0065] As an example, the flake diameter of the flake catalyst may be 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, etc., or may be within a range consisting of any of the above values.

[0066] As an example, the sheet thickness of the sheet catalyst may be 50 nm, 70 nm, 90 nm, 110 nm, 130 nm, 150 nm, 170 nm, 190 nm, 200 nm, etc., or may be a range consisting of any of the above values.

[0067] As an example, the average particle size of the active metal particles may be 2 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, etc., or may be a range consisting of any of the above values.

[0068] Therefore, the sheet-shaped catalyst provided in the present application is relatively large in size, which is beneficial to increasing the diameter of the carbon nanotube array, thereby improving the supporting force and growth length of the carbon nanotube array.

[0069] The third aspect of the present application provides a method for preparing a carbon nanotube array, the method comprising: mixing the sheet catalyst prepared by the method provided by the first aspect of the present application or the sheet catalyst provided by the second aspect of the present application with a carbon source gas for reaction, wherein the reaction temperature is 500°C-900°C, so as to obtain the carbon nanotube array. Thus, a thick and long array of carbon nanotubes is obtained, and a conductive network with excellent performance can be constructed.

[0070] According to some embodiments of the present application, a certain amount of sheet catalyst is placed in a reactor, a certain amount of carbon source gas is introduced, the reaction time is 5min-120min, and after the reaction is completed, the temperature is lowered to room temperature under inert gas protection to obtain a black fluffy carbon nanotube product.

[0071] As an example, the carbon source gas includes at least one of methane, ethylene, ethane, propylene, propane, carbon monoxide, natural gas, benzene, or toluene.

[0072] Therefore, the method for preparing carbon nanotube arrays proposed in the present application is simple and easy to operate, has a wide range of gas sources, and a low reaction temperature. Large-diameter, long-array carbon nanotube arrays can be obtained. The long-array carbon nanotubes have significant orientation, high purity (>95%), and can reach hundreds of microns in length, which is conducive to exerting excellent performance in the battery conductive network.

[0073] The fourth aspect of the present application provides a carbon nanotube array, which is prepared by the method provided in the third aspect of the present application, wherein the length of the carbon nanotube array is 20 μm-200 μm, and the number of walls of the carbon nanotubes in the carbon nanotube array is 2-30 layers.

[0074] According to some embodiments of the present application, the diameter of the carbon nanotube array is 2 μm-6 μm, and the specific surface area is 300 m 2 / g-650m 2 / g.

[0075] According to some embodiments of the present application, the carbon nanotubes in the carbon nanotube array may have a diameter of 5 nm-15 nm and a length of 20 μm-200 μm.

[0076] In the present application, the length of the carbon nanotube array and the diameter of the carbon nanotubes can be counted by SEM.

[0077] The fifth aspect of the present application provides a conductive agent, including the carbon nanotube array provided by the fourth aspect of the present application.

[0078] The sixth aspect of the present application provides a pole piece, comprising the conductive agent provided in the fifth aspect of the present application.

[0079] The seventh aspect of the present application provides a battery, comprising the electrode provided in the sixth aspect of the present application.

[0080] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0081] Example 1

[0082] (1) Select M 2+ The components are magnesium sulfate, the active N component is cobalt nitrate, M 3+ The component is chromium nitrate. Add 0.2 mol magnesium sulfate, 0.05 mol cobalt nitrate and 0.1 mol chromium nitrate solid into 250 mL water and stir evenly to form solution A.

[0083] (2) Add 0.7 mol of sodium bicarbonate to 250 mL of water and stir to form solution B;

[0084] (3) High-purity nitrogen was continuously introduced into solution A and solution B for 30 min to replace the oxygen in the solution;

[0085] (4) Add solution A and solution B dropwise and mix them simultaneously, set the temperature to 100°C, stir at 200 rpm, control the pH to 7-9 and react for 6 hours, then control the pH to 9-10 and react for 6 hours, let stand and age for 12 hours, filter the product after the reaction is complete, wash until neutral, dry the solid in a forced air drying oven at 80°C, grind and crush to obtain a flake precursor. Take 0.5 g of the flake precursor and place it in a fixed bed reactor, introduce 0.5 L / min nitrogen, heat to 650°C, continue to introduce 0.2 L / min hydrogen for pretreatment for 10 minutes, and obtain a catalyst. The distribution of active metals in the central area of ​​the catalyst is shown in Figure 2 ,Depend on Figure 2 It can be seen that the active metal particles 12 are uniformly distributed in the central area of ​​the carrier 11 .

[0086] The steps for synthesizing carbon nanotube arrays using the flake catalyst are as follows:

[0087] In a fixed bed reactor, 0.5 L / min ethylene was introduced at 650°C for 30 min to prepare a carbon nanotube array. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and a black fluffy product was collected. The product analysis results are shown in Table 1, where the carbon nanotube yield is obtained by dividing the product weight by the weight of the flake catalyst put into the reactor.

[0088] Example 2

[0089] (1) Select M 2+ The active N component is ferrous sulfate, M 3+ The component is aluminum sulfate. Add 0.2 mol magnesium sulfate, 0.08 mol ferrous sulfate and 0.1 mol aluminum sulfate solid into 250 mL water and stir evenly to form solution A.

[0090] (2) Add 3 mol of urea to 250 mL of water and stir to form solution B;

[0091] (3) High-purity nitrogen was continuously introduced into solution A and solution B for 30 min to replace the oxygen in the solution;

[0092] (4) Add solution A to solution B and mix, set the temperature to 105°C, stir at 200 rpm, control the pH to 7-9, react for 6 h, then control the pH to 9-10, react for 6 h, and let stand for 12 h. After the reaction is complete, filter the product, wash until neutral, take the solid and dry it at 80°C in a forced air drying oven, grind and crush to obtain a flake precursor. The structure of the precursor is as follows: Figure 3 As shown by Figure 3 It can be seen that the precursor has a larger flake diameter. 0.5 g of the flake precursor was placed in a fixed bed reactor, 0.5 L / min of nitrogen was introduced, the temperature was raised to 750 ° C, and 0.2 L / min of hydrogen was introduced for pretreatment for 10 minutes to obtain a catalyst. The calcination and pretreatment process did not affect the size of the catalyst flake layer. The size of the catalyst flake layer remained consistent with the precursor, and the flake diameter remained large.

[0093] The steps for synthesizing carbon nanotube arrays using the flake catalyst are as follows:

[0094] In a fixed bed reactor, 0.5 L / min ethylene was introduced at 750°C for 60 min to prepare carbon nanotube arrays. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and a black fluffy product was collected. The product analysis results are shown in Table 1.

[0095] Example 3

[0096] (1) Select M 2+ The active N component is ferrous chloride, M 3+The component is aluminum nitrate. Add 0.2 mol of magnesium nitrate, 0.02 mol of ferrous chloride and 0.1 mol of aluminum nitrate solid into 250 mL of water and stir evenly to form solution A.

[0097] (2) Add 0.7 mol of sodium hydroxide to 250 mL of water and stir to form solution B;

[0098] (3) High-purity nitrogen was continuously introduced into solution A and solution B for 30 min to replace the oxygen in the solution;

[0099] (4) Add solution B to solution A and mix, set the temperature to 95°C, stir at 200 rpm, control the pH to 7-9, react for 6 h, then control the pH to 9-10, react for 6 h, let stand for 12 h, filter the product after the reaction is complete, wash until neutral, take the solid and dry it at 80°C in a forced air drying oven, grind and crush to obtain a flake precursor, Figure 4 It can be seen that the Fe metal is distributed in the central area of ​​the precursor. 0.5g of the flake precursor was placed in a fixed bed reactor, 0.5L / min of nitrogen was introduced, the temperature was raised to 700°C, and 0.2L / min of methane was introduced for pretreatment for 10 minutes to obtain a catalyst. Affected by the distribution of Fe metal on the precursor, the Fe metal particles on the catalyst were also distributed in the central area of ​​the carrier.

[0100] The steps for synthesizing carbon nanotube arrays using the flake catalyst are as follows:

[0101] In a fixed bed reactor, 0.5 L / min propylene was introduced at 700°C for 45 min to prepare a carbon nanotube array. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and a black fluffy product was collected. The structure of the carbon nanotube is as follows Figure 5 As shown by Figure 5 It can be seen that a long array of carbon nanotubes was prepared. The product analysis results are shown in Table 1.

[0102] Example 4

[0103] A sheet catalyst for growing long array carbon nanotubes and a preparation method thereof, comprising the following steps:

[0104] (1) Select M 2+ The active N component is magnesium nitrate, and the active N component is nickel nitrate. 3+ The component is aluminum nitrate. Add 0.2 mol of magnesium nitrate, 0.1 mol of nickel nitrate and 0.1 mol of aluminum nitrate solid into 250 mL of water and stir evenly to form solution A.

[0105] (2) Add 0.9 mol of aqueous ammonia to 250 mL of water and stir to form solution B;

[0106] (3) High-purity nitrogen was continuously introduced into solution A and solution B for 30 min to replace the oxygen in the solution;

[0107] (4) Add solution B to solution A and mix, set the temperature to 100°C, stir at 200 rpm, control the pH to 7-9 and react for 6 hours, then control the pH to 9-10 and react for 6 hours, let stand and age for 12 hours, filter the product after the reaction is complete, wash to neutrality, take the solid and dry it at 80°C in a forced air drying oven, grind and crush to obtain a flake precursor. Take 0.5g of the flake precursor and place it in a fixed bed reactor, introduce 0.5L / min nitrogen, raise the temperature to 800°C, and continue to introduce 0.2L / min carbon monoxide for pretreatment for 10 minutes to obtain a catalyst.

[0108] The steps for synthesizing carbon nanotube arrays using the flake catalyst are as follows:

[0109] In a fixed bed reactor, 0.5 L / min natural gas was introduced at 800°C for 120 min to prepare carbon nanotube arrays. After the reaction, the temperature was lowered to room temperature under inert gas protection, and black fluffy products were collected. The structure of the carbon nanotubes is as follows Figure 6 As shown in the figure, the carbon nanotube array grows from the inner area of ​​the catalyst, and the outer area of ​​the catalyst protects the carbon nanotube array. The product analysis results are shown in Table 1.

[0110] Thermogravimetric analysis curve of carbon nanotube raw powder is shown in Figure 8 ,Depend on Figure 8 It can be seen that the ash content in the raw carbon nanotube powder is only 2.33%, and the catalyst has a higher carbon nanotube yield.

[0111] Comparative Example 1

[0112] On the basis of Example 3, only the concentration of the precipitant and the pH control range during the precipitation reaction were changed. The specific steps are as follows:

[0113] (1) Select M 2+ The active N component is ferrous chloride, M 3+ The component is aluminum nitrate. Add 0.2 mol of magnesium nitrate, 0.02 mol of ferrous chloride and 0.1 mol of aluminum nitrate solid into 250 mL of water and stir evenly to form solution A.

[0114] (2) Add 0.9 mol of sodium hydroxide to 250 mL of water and stir to form solution B;

[0115] (3) High-purity nitrogen was continuously introduced into solution A and solution B for 30 min to replace the oxygen in the solution;

[0116] (4) Add solution B to solution A and mix, set the temperature to 95°C, stir at 200 rpm, control the pH to 9-10, react for 12 hours, and allow to stand for 12 hours. After the reaction is complete, filter the product, wash until neutral, take the solid and dry it at 80°C in a forced air drying oven, grind and crush it to obtain a sheet precursor. The steps of using the sheet precursor to obtain the catalyst are the same as those in Example 3. The catalyst sheet has a small diameter (0.7 μm-1.5 μm), and the active metal does not have a regional distribution, but is evenly distributed on the catalyst sheet.

[0117] The steps of synthesizing a carbon nanotube array using the sheet catalyst are the same as those in Example 3. The structure of the carbon nanotube is shown in Figure 7 The grown carbon nanotube array is distributed on the entire catalyst layer, and the length of the carbon nanotube array is 1μm-10μm and the diameter is 0.7μm-1.5μm.

[0118] Comparative Example 2

[0119] On the basis of Example 3, only the mixing method of solutions A and B, the precipitation reaction temperature and the pH control range during the precipitation reaction were changed. The specific steps are as follows:

[0120] (1) Select M 2+ The active component is magnesium nitrate, and the active component M is ferrous chloride. 3+ The component is aluminum nitrate. Add 0.2 mol of magnesium nitrate, 0.02 mol of ferrous chloride and 0.1 mol of aluminum nitrate solid into 250 mL of water and stir evenly to form solution A.

[0121] (2) Add 0.7 mol of sodium hydroxide to 250 mL of water and stir to form solution B;

[0122] (3) High-purity nitrogen was continuously introduced into solution A and solution B for 30 min to replace the oxygen in the solution;

[0123] (4) Add solution A to solution B and mix, set the temperature to 80°C, stir at 200 rpm, control the pH to 9-12, react for 12 hours, and let stand for 12 hours. After the reaction is completed, filter the product, wash it to neutrality, take the solid and dry it in a forced air drying oven at 80°C, grind it and crush it to obtain a flake precursor. The steps of using the flake precursor to obtain the catalyst are the same as those in Example 3. The catalyst flakes have a small diameter (0.2 μm-0.5 μm), and the active metal is distributed regionally in the center of the layer plate.

[0124] The steps of synthesizing a carbon nanotube array using the sheet-like catalyst are the same as those in Example 3. The grown carbon nanotube array has regional growth, and the length of the carbon nanotube array is 1 μm-5 μm, and the diameter is 0.1 μm-0.3 μm.

[0125] The test results of Example 1 to Example 4, Comparative Example 1 and Comparative Example 2 are shown in Table 1.

[0126] Table 1

[0127]

[0128]

[0129] According to the results of the thermogravimetric test, the catalyst yield = carbon nanotube product mass (thermal weight loss mass) / ash mass (residual mass) × 100%.

[0130] In the present application, the test method for the average diameter of the catalyst layer is the electron microscopy statistical method.

[0131] The basis for judging whether the carbon nanotubes grow regionally is the electron microscopy characterization results.

[0132] The test method for the surface density of regional active metal particles is the electron microscope statistical method.

[0133] The length of the carbon nanotube array is measured by electron microscopy statistics.

[0134] The ash content was determined by thermogravimetric analysis.

[0135] As can be seen from Examples 1-4, by controlling the reaction temperature, pH value, type and concentration of the precipitant during the coprecipitation process, the degree of supersaturation of the solution can be regulated to obtain a large-sized lamellar structure; by controlling the pH value, the order of metal precipitation can be regulated so that the active metal is distributed only in the central area of ​​the carrier. For the sheet catalyst based on the double metal hydroxide, under different operating conditions, the method of the present invention can achieve batch preparation of long array carbon nanotubes. The source of the metal component includes a variety of metal salts, indicating the convenience of the preparation operation of the sheet catalyst, and increasing M 2+ The added amount of the components can significantly increase the yield of the long multi-walled carbon nanotube array. The sheet catalyst prepared by the invention is suitable for growing long array carbon nanotubes in different types of reactors, and has a certain industrial scale-up production basis.

[0136] Combining Comparative Example 1 and Example 3, it can be seen that by changing the concentration of the precipitant and the pH range during the precipitation reaction, the solution supersaturation and the metal precipitation order can be regulated, thereby affecting the catalyst sheet diameter, the distribution position of the active metal and the density of the active metal particles. When the catalyst sheet diameter is small, the diameter of the grown carbon nanotube array is limited by the catalyst sheet diameter and is small, and the active metal is evenly distributed on the catalyst sheet layer, so that the surface density of the metal particles is correspondingly reduced, which leads to the limited length of the carbon nanotube array grown in Comparative Example 1. In contrast, the catalyst sheet diameter after regulation in Example 3 is larger, and the active metal is regionally concentrated to form a higher surface density, thereby promoting the increase in the length of the carbon nanotube array with a greater synergistic effect.

[0137] Combining Comparative Example 2 and Example 3, it can be seen that by changing the mixing method of solutions A and B, the precipitation reaction temperature and the pH control range during the precipitation reaction, the solution supersaturation can be adjusted, thereby affecting the catalyst sheet diameter. When the catalyst sheet diameter is small, a longer carbon nanotube array cannot be obtained.

[0138] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for preparing a sheet catalyst, characterized in that: include: Will contain M 2+ Salt solution containing M 3+ A salt solution containing Q ions is mixed once to form a first mixed solution, wherein the M 2+ Including Mg 2+ 、Zn 2+ , Ca 2+ , Mn 2+ At least one of the M 3+ Including Cr 3+ 、Al 3+ 、Ru 3+ At least one of the Q ions includes Fe 2+ , Fe 3+ 、Co 2+ 、Co 3+ 、Ni 2+ , Cu 2+ At least one of; mixing the precipitant and the solvent to form a second mixed solution; The first mixed solution and the second mixed solution are mixed once to form a third mixed solution, and a precursor is obtained by coprecipitation, wherein the temperature of the third mixed solution during the coprecipitation process is 90° C.-150° C., and the pH of the third mixed solution is 4-12; The precursor is calcined and reduced to obtain the sheet-like catalyst.

2. The method according to claim 1, characterized in that Satisfy at least one of the following conditions: The molar concentration of the precipitant solution is 0.1 mol / L-20 mol / L; The precipitant includes at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate, ammonium bicarbonate, urea, and ammonia water.

3. The method according to claim 2, characterized in that The first mixed solution contains M 2+ 、M 3+ The sum of the concentrations of Q ions is 0.005mol / L-2mol / L.

4. The method according to claim 3, characterized in that The first mixed solution contains M 2+ With M 3+ The molar ratio of Q ions and M in the first mixed solution is 0.1-10. 3+ The molar ratio is 0.01-2.

5. The method according to claim 1, characterized in that: At least one of the following conditions is met: The calcination atmosphere is an inert gas or air; The calcination temperature is 400°C-900°C; The heating rate of the calcination is 1°C / min-20°C / min.

6. The method according to claim 1, characterized in that The reduction process includes: pre-treating the calcined precursor by a pre-treatment gas, wherein the pre-treatment satisfies at least one of the following conditions: The pretreatment temperature is 400°C-900°C; The pretreatment time is 1 min-60 min.

7. A sheet catalyst, characterized in that: The catalyst is prepared by the method described in any one of claims 1 to 6, wherein the sheet-like catalyst comprises a carrier, the surface of the carrier comprises a central region and an edge region, and the active metal particles are only distributed in the central region.

8. The sheet catalyst according to claim 7, characterized in that The sheet diameter of the sheet catalyst is 2 μm-10 μm, the sheet thickness is 50 nm-200 nm, and the average particle diameter of the active metal particles is 2 nm-50 nm.

9. A method for preparing a carbon nanotube array, characterized in that: include: The flake catalyst prepared by the method according to any one of claims 1 to 6 or the flake catalyst according to claim 7 or 8 is mixed with a carbon source gas for reaction at a temperature of 500° C. to 900° C. to obtain the carbon nanotube array.

10. A carbon nanotube array, characterized in that: The carbon nanotube array is prepared by the method according to claim 9, wherein the length of the carbon nanotube array is 20 μm-200 μm, and the number of walls of the carbon nanotubes in the carbon nanotube array is 2-30 layers.

11. A conductive agent, characterized in that: Comprising the carbon nanotube array assembly as claimed in claim 10.

12. A pole piece, characterized in that: Includes the conductive agent according to claim 11.

13. A battery, characterized in that: Including the pole piece as claimed in claim 12.